ESTUDO TEÓRICO DA INTERAÇÃO ENTRE HIDRAZINA E COMPLEXOS TETRAAZAMACROCICLOS DE FERRO E MANGANÊS. - SILVA, Francivaldo Santos da (2018)
In this work a theoretical study was carried out by DFT using the B3LYP functional with set of LANL2DZ / 6-31G* base functions for interaction of hydrazine and iron and manganese metal complexes. The calculations for the system were performed by the Gaussian 09 program to verify parameters such as: bond length and angles, charge distribution, electron population, vibrational frequencies and binding order for hydrazine, complexes and adducts (complex-hydrazine interaction). The complexes studied were tetraaza[14]anulene ligands (TAA: Tetraaza[14]anulene; DBTAA: Dibenzo[b,i]-[1,4,8,11]-tetraaza[14] anulene; TMTAA: 5,7,12,14-tetramethyl-tetraaza [14] anulene; TMDBTAA1: 5,7,12,14-tetramethyl-dibenzo[b,i]-[1,4,8,11]-tetraaza[14]anulene and TMDBTAA2: 2,3,9,10-tetramethyl-dibenzo[b,i]-[1,4,8,11]-tetraaza[14]anulene), porphyrin (P) and phthalocyanine (Pc) at their most stable spin multiplicities. Calculations showed that the most stable multiplicity of the iron complexes was triplet and for the manganese the quartet, except for the MnP complex which was sextet. After interaction with the hydrazine, the more stable multiplicity of the FeTAA'sN2H3 -adducts passed to the quintet and that of the adducts MnTAA's- N2H3 -passed to sextet. The Fe-porphyrin adduct changed its multiplicity to quintet and that of Mn remained sextet. Already the iron phthalocyanine adduct changed the multiplicity to quintet and that of Mn to doublet. The analyzed parameters show a tendency for oxidation, since it was verified that between the nitrogen atoms (N1–N2) of the complexed hydrazine there was decrease in bond length, increase of Mulliken and NBO charges and decrease of the electron population after formation of adducts. However, the most favorable complexes for the redox process were phthalocyanines and porphyrins, which also had lower HOMO-LUMO energy gap and higher catalytic activity compared to tetraaza [14] anulenes.